2024
DOI: 10.1097/md.0000000000036186
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the systemic immuno-inflammatory index in critically ill patients with vertebral fractures

Kaiya Zhang,
Xia Li,
Yaoyao Xu
et al.

Abstract: Inflammation plays a critical role in vertebral fractures. However, there is a lack of sufficient evidence regarding the prognostic significance of the systemic immuno-inflammatory index (SII), a novel marker of systemic inflammation, in patients with vertebral fractures. In this study, we aimed to assess the predictive value of SII in critically ill patients with vertebral fractures. The data were from the Medical Information Mart for Intensive Care III (MIMIC-III) version 1.4 and Wenzhou Hospital of Traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Further, a prospective study involving 290 participants showed that in elderly patients who underwent hip fracture surgery, a strong association was observed between SII and increased mortality due to any cause ( 5 ). In addition, several studies have demonstrated the role of SII in reflecting systemic inflammation and disease severity ( 36 , 37 ), particularly the diagnostic significance of SAPSII in orthopedic diseases ( 38 , 39 ). These studies suggested that SII showed potential for predicting clinical outcomes in critically ill elderly individuals with hip fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a prospective study involving 290 participants showed that in elderly patients who underwent hip fracture surgery, a strong association was observed between SII and increased mortality due to any cause ( 5 ). In addition, several studies have demonstrated the role of SII in reflecting systemic inflammation and disease severity ( 36 , 37 ), particularly the diagnostic significance of SAPSII in orthopedic diseases ( 38 , 39 ). These studies suggested that SII showed potential for predicting clinical outcomes in critically ill elderly individuals with hip fractures.…”
Section: Discussionmentioning
confidence: 99%